Clean Cooking Energy Transition: Feasibility Study on Biogas Adoption Among Low-Income Households in Anambra State - Onwusuru, Ijeoma Madonna; Agbo, Nnaemeka Martin; Nnajiofor, Francisca N. (Journal of Research in Industrial Technology and Educational Studies, 2025)
This study investigates the feasibility of adopting biogas stove technology as a clean cooking energy alternative among low-income households in Anambra State, Nigeria. In rural communities in Anambra State, households commonly utilize various cooking energies, including firewood, charcoal, kerosene, and LPG (Liquefied Petroleum Gas) among others. Using a survey design, data were collected from 251 respondents across select communities. Findings reveal that although LPG is a common fuel source, a significant number of households still rely on kerosene and charcoal, underscoring ongoing energy poverty and environmental health risks. This implies that persistent use of polluting fuels despite LPG access suggests economic fragility and vulnerability to energy insecurity. While awareness of biogas technology is moderate (61.8%), a sizable proportion remains uninformed. Key factors influencing adoption include perceived safety, financial and technical support, and evidence of successful use in rural settings. Notably, 87.3% of respondents expressed willingness to adopt biogas, conditional on these concerns being addressed. Major barriers to transition include safety apprehensions, lack of familiarity, and cost constraints. The study highlights the need for targeted awareness campaigns, financial incentives, and community demonstration projects to facilitate a just and inclusive clean energy transition in Anambra State.
Keywords: Biogas adoption; clean cooking energy; low-income households; energy transition; Anambra State